Histological and biochemical study on hypoglycemic and antihyperlipidemic effects of aqueous extract of Cynodon dactylon in streptozotocin-induced diabetic rats - Madhan Kumar SJ; Christildafelicia Jebakani; S.Sundarapandian (International Journal of Phytomedicine, 2015)
Cynodon dactylon has been mentioned in ayurvedic system of Indian medicine to be of value in the treatment of diabetes mellitus. The purpose of this study was to investigate the possible hypoglycemic effects of aqueous extract of the whole plant of Cynodon dactylon on blood glucose, plasma insulin, serum lipid profiles and possible histopathological changes in the pancreatic tissue of streptozotocin induced diabetic rats. Type 1 diabetes was induced by streptozotocin (STZ) in rats. One sub-group of rats, received glibenclamide treatment and another received Cynodon extract Treatment for 45 days respectively. Blood was analyzed for fasting blood glucose, insulin levels and lipid profiles after treatment. Histopathological sectional studies of the pancreatic islets were done. Treatment of the animals with the aqueous extract from plant at a dose of (500 mg/kg body weight) for 45 days resulted in significant reduction in blood glucose, cholesterol, triglycerides, low-density lipoprotein, and very- low - density lipoprotein in STZ diabetic rats. These biochemical parameters were correlated with the histopathological changes observed in the pancreatic islets of STZ diabetic rats, which structurally proved the effectiveness of the aqueous extract of C.dactylon in STZ diabetic rats. The obtained biochemical and histopathological results confirmed the hypoglycemic and antihyperlipidemic effects of aqueous extract of the C.dactylon in experimental model of diabetic animals. Cynodon dactylon may be useful as a natural supplementary medicine in the treatment of diabetes and its complications.